2011
DOI: 10.1149/1.3577749
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrochemical Investigation of Hydrogen Absorption and Dissolution Behavior of MnS Inclusions in Carbon Steel

Abstract: Microelectrochemical polarization and silver decoration techniques were performed on the small area with and without MnS inclusions. MnS inclusions were found to be partially dissolved in the potential range from 0.15 to -0.45 V (vs. Ag/AgCl, 3.33 M KCl) in a boric-borate buffer (pH 8.45) with 10 mM NaCl, whereas the entire surface of the inclusions was dissolved below and above this potential range. Silver deposition occurred only on and around MnS inclusions below -0.2 V, which generally corresponded to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…0.2–1 μm in size) more directly (i.e., the inclusions constitute all or most of the probed area). Large MnS inclusions have previously been shown to be responsible for enhanced hydrogen trapping on steel surfaces, which can lead to hydrogen-induced cracking, , and blistering at these sites . Our results further emphasize the importance of inclusions as highly active cathodic sites on polycrystalline low carbon steel.…”
Section: Resultssupporting
confidence: 74%
“…0.2–1 μm in size) more directly (i.e., the inclusions constitute all or most of the probed area). Large MnS inclusions have previously been shown to be responsible for enhanced hydrogen trapping on steel surfaces, which can lead to hydrogen-induced cracking, , and blistering at these sites . Our results further emphasize the importance of inclusions as highly active cathodic sites on polycrystalline low carbon steel.…”
Section: Resultssupporting
confidence: 74%
“…Thus, the HIC susceptibility of the steel is reduced. Generally, the effect of the dispersion of sufficiently small MnS inclusions, such as those found in this work, on the hydrogen concentration is ignored . The authors' previous work did find that there existed direct correlations between the size of inclusions contained in steels and their HIC susceptibility …”
Section: Discussionmentioning
confidence: 69%
“…As indicated by Du et al and Pérez Escobar et al, when substantial strip‐shaped MnS inclusions exist in the steels, the interfaces between the inclusions and the steel matrix usually become the hydrogen trapping sites, resulting in that an increased HIC susceptibility. Muto et al also found that the presence of MnS inclusions in the steel enhanced the absorption of hydrogen atoms, and accelerated the formation of HIC cracks. Domizzi studied the influences of S content and the amount and distribution of MnS inclusions on the steel HIC, and found that bigger strip‐shaped MnS inclusions resulted in a higher susceptibility of the steel to HIC.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation